THE PANDEMIC AND HOMILETICS 101: A REFLECTION - S. Hoezee (Acta Theologica)
The global pandemic of COVID-19 across the year 2020 afforded pastors everywhere an opportunity to engage in some critical reflection on their homiletic practices. The dual challenges of no longer being able to preach to a physically present congregation and of preaching during a time of significant fear, stress, and sorrow revealed to many preachers aspects of preaching of which they had not previously been aware. This article suggests that some of what was discovered during this unusual season provides correctives for the way in which homiletics and preaching have been practised in many places and that some of these correctives should endure in the preaching life of the church long after the pandemic has passed.